Reconstruction of the Management, Utilization and Sale of Waqf Property in Indonesia from the Perspective of Maqāṣid Ash-Shari'ah - Kurniati, Herlina; Muslim, Muslim (Universitas Islam Negeri Raden Intan Lampung, 2024)
The issue of selling waqf objects has different opinions among scholars, as some scholars of the Māliki and Shāfi'i schools of thought are of the opinion that waqf assets cannot be sold or exchanged. Meanwhile, according to the Hanbali school of thought, waqf assets may be traded provided that the waqf assets are no longer productive and the conditions require it. Therefore, because this waqf doctrine is included in the ijtihādiyah issue, it is not a matter of worship (ta'abbūdi). The focus of the problem in this research is how to reconstruct the management, empowerment and trading of waqf assets in Indonesia from the perspective of Maqāṣid Ash- Shari'ah. The method used in this research is typologically, this research is a model of Islamic legal research categorized as qualitative research. Qualitative research is descriptive qualitative, this research is included in the category of library research which aims to explore and search for maqāṣîd ash-sharî'ah concepts from classical and contemporary uṣûl al-fiqh experts, whose data are obtained from searching for reading sources to obtain primary legal materials, secondary legal materials, and tertiary materials. The results of the research can be concluded that in Indonesia the regulations governing waqf issues can be found in Law No. 41 of 2004 concerning Waqf, which was signed by the President of the Republic of Indonesia (SBY) on October 2, 2004. A few years later, PP No. 42/2006 was issued to implement the law. From the perspective of maqāṣid ash-shari'ah, the management and utilization, including selling waqf assets that are no longer productive, badly damaged, and have almost lost their usefulness, is basically the purpose of the waqf asset itself, which is to fulfill the needs and interests of the community.Keywords: ijtihādiyah; Maqāṣid Ash-Shari'ah; Reconstruction; Productive Waqf